Psychometric properties of parent and child reported sleep assessment tools in children with cerebral palsy: A systematic review - Bautista, M.; Whittingham, K.; Edwards, P.; Boyd, Roslyn (Wiley-Blackwell Publishing Ltd., 2017)
Aim: To determine whether any parent and child report sleep measure tools have been validated in children aged 0-18 years with cerebral palsy (CP). Method: A systematic search of five databases was performed up to June 2017. Studies were included if a sleep measure tool was used to evaluate sleep in children 0-18 years with CP based on international classifications of sleep. Sleep measures were assessed for psychometric data in children with CP. Results: Only one paper which used the Schlaffragebogen für Kinder mit Neurologischen und Anderen Komplexen Erkrankungen (SNAKE) questionnaire met the study criteria. The four other measures frequently used in children with CP had no psychometric data available for their use in children with CP. The SNAKE questionnaire has been validated only in children with CP in Gross Motor Function Classification System level V. The Sleep Disturbance Scale for Children and the Pediatric Sleep Questionnaire had the strongest psychometric properties in typically developing children, but has not yet been validated in children with CP. Interpretation: Current sleep measures being administered in typically developing children are also often used in children with CP, but have not been well validated in this group of children.